2006
DOI: 10.1111/j.1572-0241.2006.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Gastric Acid Secretion May Be Important for the Development of Gastroesophageal Junction Adenocarcinoma in Japanese People, Irrespective of the H. pylori Infection Status

Abstract: Preservation of gastric acid secretion may be important for the development of GE junction adenocarcinoma in Japanese people, irrespective of the H. pylori infection status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 43 publications
2
37
1
1
Order By: Relevance
“…The reason for the unreliability of serum markers in detecting diffuse-type cancer is that most of these cancers occur without gastric atrophy, as reported by Inomata et al [32]. This suggests that normal acid secretion may be important for the development of diffuse-type adenocarcinoma, particularly at the gastroesophageal junction.…”
Section: Discussionmentioning
confidence: 94%
“…The reason for the unreliability of serum markers in detecting diffuse-type cancer is that most of these cancers occur without gastric atrophy, as reported by Inomata et al [32]. This suggests that normal acid secretion may be important for the development of diffuse-type adenocarcinoma, particularly at the gastroesophageal junction.…”
Section: Discussionmentioning
confidence: 94%
“…With this method, we measured gastric acid secretion level in a series of patients with various upper GI diseases such as peptic ulcer, reflux esophagitis, Barrett's esophagus, and superficial gastric or esophageal cancer (Iijima et al 1998(Iijima et al , 2000(Iijima et al , 2005(Iijima et al , 2010Koike et al 2001;Abe et al 2004;Inomata et al 2006;Iwai et al 2013). In this study, we retrospectively analyzed the accumulated database based on our previous studies and investigated the correlation between gastric acid secretion levels and serum PG values.…”
Section: Introductionmentioning
confidence: 99%
“…As found in other studies, a study from Japan showed that H. pylori infection may play a protective role in the development of BE (especially LSBE), although the number of patients evaluated was limited [90]. The same group proposed that the preservation of gastric acid secretion might be important for the development of adenocarcinoma at the EGJ (including EAC) in Japanese people, irrespective of the H. pylori infection status [91]. Namely, there may be two distinct types of cancer at the EGJ-EAC (BE cancer) associated with high gastric acid secretion and reflux of gastric acid into the esophagus and EGJ adenocarcinoma (non-BE cancer) resembling distal gastric cancer associated with gastric atrophy and low gastric acid secretion [92,93].…”
Section: H Pylori Infection and Carcinogenesismentioning
confidence: 78%